2022
DOI: 10.1002/pen.25990
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the titanium dioxide nanoparticles on the morphology and degradation of polyamide 6 prepared by anionic ring‐opening polymerization

Abstract: Thermoplastic Resin Transfer Molding can be used to produce polyamide 6-based composites from ε-caprolactam by anionic ring-opening polymerization. However, the service life and applicability of these composites are limited because polyamide 6 is sensitive to UV radiation. Therefore, we analyzed the effect of nanosized titanium dioxide on the UV stability of polyamide 6 produced from ε-caprolactam. Despite the very low viscosity of caprolactam, we dispersed nanoparticles homogeneously in it before producing po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 65 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…We performed ATR-FTIR (Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy) studies on the samples with poor adhesion (Fig. 6), and showed that both the surface and the base layer had characteristic peaks typical of polyamide 6: hydrogen-bonded N-H stretching at 3295 cm −1 , C-H stretching and tension vibration at 2924 and 2854 cm −1 , respectively, amide I (C= O) vibration at 1634 cm −1 and amide II (N-H and C-N combination) vibration at 1537 cm −1 [35,36]. For the samples taken from the interface, we clearly showed that poor polymerization took place there.…”
Section: Evaluation Of the Applicability Of The Technologymentioning
confidence: 99%
“…We performed ATR-FTIR (Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy) studies on the samples with poor adhesion (Fig. 6), and showed that both the surface and the base layer had characteristic peaks typical of polyamide 6: hydrogen-bonded N-H stretching at 3295 cm −1 , C-H stretching and tension vibration at 2924 and 2854 cm −1 , respectively, amide I (C= O) vibration at 1634 cm −1 and amide II (N-H and C-N combination) vibration at 1537 cm −1 [35,36]. For the samples taken from the interface, we clearly showed that poor polymerization took place there.…”
Section: Evaluation Of the Applicability Of The Technologymentioning
confidence: 99%
“…21,22 However, biocompatibility, photocatalytic ability, and semi-conducting properties require a crystalline phase. 23 Two important properties of TiO 2 are its photocatalytic and antibacterial abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the production of electron–hole pairs, surface adsorption and desorption processes, and redox processes influence the photocatalytic properties 21,22 . However, biocompatibility, photocatalytic ability, and semi‐conducting properties require a crystalline phase 23 . Two important properties of TiO 2 are its photocatalytic and antibacterial abilities.…”
Section: Introductionmentioning
confidence: 99%
“…Caprolactam is an organic compound belonging to cyclic amides or lactams with the formula C 6 H 11 NO, widely used in different industries such as the automotive, textile, and electronic industries and, the production of polyamides such as Nylon 6, among others [ 1 , 2 ]. Caprolactam can be obtained using different pathways of strains that use toluene, benzene, and cyclohexane that react by Beckmann rearrangement and the formation of cyclohexanone as an intermediate [3] , [4] , [5] , [6] .…”
Section: Introductionmentioning
confidence: 99%